Manajemen Strategi Pembiayaan Dalam Organisasi Sekolah - Ilham Yahya Romandoni; Sulistyorini Sulistyorini; Chusnul Chotimah (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2024)
Research on Financing Strategy Management in School Organizations is motivated by the need for a strategy in managing school financing based on operational needs that have been designed. This research uses research methodslibrary research. With a descriptive qualitative approach. The data analysis technique was carried out using descriptive analysis. The data sources for this research come from scientific articles and books. The results of this research show that the strategy for managing school organization finances starts from planning, bookkeeping, spending, supervision and financial accountability, where the financial sources come from the APBN, APBD, parents and other sources. In managing financing, it must be based on the school's operational needs which include financing all activities, financing books, financing exams, financing consumables and school maintenance.